PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA WORDWALL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SEKOLAH DASAR - Damayanti, Delva; Wahyuni, Rika; Rosmaiyadi, Rosmaiyadi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the implementation of the cooperative learning model Make a Match assisted by Wordwall media on students’ mathematical problem-solving skills in fraction material among fifth-grade students at SDN 1 Singkawang. The research employed a quantitative approach using a Nonequivalent Posttest-Only Control Group Design. The sample consisted of two groups: class V-A as the experimental group (26 students) and class V-B as the control group (26 students). The sampling technique used was non-probability purposive sampling. Data were collected through essay tests on mathematical problem-solving ability and student response questionnaires. Data were analyzed using an independent sample t-test and percentage analysis. The results indicated that (1) there was a significant difference in students’ mathematical problem-solving skills between the experimental class using the Make a Match model assisted by Wordwall and the control class using direct instruction, with a t-value of 7.92006 > 2.0085; (2) students gave positive responses toward the learning model, with a percentage score of 85.19%, categorized as very good. Therefore, it can be concluded that the Make a Match cooperative learning model assisted by Wordwall media effectively improves students’ mathematical problem-solving skills in fraction learning.